Legal Analysis of Intellectual Property Rights Protection in Musical Works Produced Through Artificial Intelligence: A Case Study of Suno AI Platform Implementation - Angga Sandhika Raharjo; Andriyanto Adhi Nugroho (Jurnal Daulat Hukum, 2025)
The rapid development of Artificial Intelligence (AI) technology has significantly transformed the fields of art and creative industries, particularly in musical creation. One of the most notable AI platforms capable of automatically generating music is Suno AI, which raises legal debates regarding its legal status and copyright protection for AI-generated works. This study aims to analyze the legal standing of Suno AI as a creator and examine the legal responsibilities related to musical works produced through artificial intelligence within the framework of Intellectual Property Rights (IPR). The research employs a normative juridical method with a statutory and conceptual approach, using data derived from legislation, legal literature, and relevant national and international case studies. The findings indicate that Suno AI cannot be recognized as a legal subject or creator, as it lacks consciousness and legal personality as required by Article 1 paragraph (2) jo. Article 31 of Law No. 28 of 2014 concerning Copyright. Therefore, AI functions merely as a technological tool, while legal rights and responsibilities rest entirely on humans, namely developers or users who control the system. In cases of copyright infringement, as stipulated in Articles 34 and 112 of the Copyright Law, human operators of the AI system bear legal responsibility, not the AI itself. Cases such as the lawsuit against Suno AI and Udio AI in the United States, as well as instances of AI-based music fraud in Indonesia, highlight the urgent need for adaptive and comprehensive legal regulations. This study concludes that Indonesia must establish a comprehensive legal framework on AI-generated creations to ensure legal certainty, protect the moral and economic rights of human creators, and promote the ethical and responsible use of AI technology in the music industry.